é€šè¿‡ç›´æŽ¥æ•™å¦æ³•è§£å†³ä¸¹å¤§ä¸æ–‡ç³»2013çº§çš„å¤§å¦ç”Ÿä½¿ç”¨ â€œæ¯”/ä¸æ¯”â€å’Œâ€œæœ‰/æ²¡æœ‰â€æ¯”è¾ƒå¥çš„å›°éš¾ - Sari, Novita; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
æ‘˜è¦ ï¼šæ¯”è¾ƒå¥æ˜¯æ—¥å¸¸äº¤é™…ä¸å¸¸ç”¨çš„å¥å¼ä¹‹ä¸€ï¼Œåœ¨æ±‰è¯ä¸å¸¸ç”¨çš„æ¯”è¾ƒå¥æœ‰ â€œæ¯”â€å—æ¯”è¾ƒå¥å’Œâ€œæœ‰â€æ¯”è¾ƒå—å¥ã€‚æ¤å¤–ï¼Œæ¯”è¾ƒå¥ä¹Ÿæ˜¯å¯¹å¤–æ±‰è¯è¯æ³•çš„æ•™å¦é‡ç‚¹ï¼Œå› ä¸ºå¯¹äºŽæ±‰è¯ä½œä¸ºç¬¬äºŒè¯è¨€çš„å¦ç”Ÿæ¥è¯´ï¼Œå¦ä¹ æ¯”è¾ƒå¥çš„æ—¶å€™å—åˆ°äº† æ¯è¯çš„å½±å“ï¼Œå¯¼è‡´å¦ç”Ÿåœ¨ä½¿ç”¨æ¯”è¾ƒå¥ä¹‹æ—¶å‡ºçŽ°äº†ä¸åŒçš„åè¯¯ã€‚ç¬”è€…é‡‡ç”¨ç›´æŽ¥æ•™å¦æ³•å¯¹ä¸¹å¤§ä¸æ–‡ç³»2013çº§Aççš„å¦ç”Ÿè¿›è¡Œâ€œæ¯”/ä¸æ¯”â€ä¸Žâ€œæœ‰/æ²¡æœ‰â€æ¯”è¾ƒå¥çš„æ•™å¦ï¼Œå¹¶ä¸”é‡‡ç”¨æµ‹è¯•æ³•äº†è§£è¯¥çå¦ç”Ÿå¦ä¹ å‰ä¸Žå¦ä¹ åŽçš„æƒ…å†µï¼Œä»¥è¿›è¡Œå¯¹æ¯”ã€‚å¯¹æ¯”ç»“æžœæ˜¾ç¤ºï¼Œå¦ä¹ åŽçš„æˆç»©æ˜Žæ˜¾æé«˜äº†ï¼Œè¿™è¯´æ˜Žç›´æŽ¥æ•™å¦æ³•é€‚åˆç”¨äºŽè¿›è¡Œâ€œæ¯”/ä¸æ¯”â€ä¸Žâ€œæœ‰/æ²¡æœ‰â€æ¯”è¾ƒå¥çš„æ•™å¦ï¼Œå› ä¸ºç›´æŽ¥æ•™å¦æ³•å…·æœ‰ç›´è§‚çš„ç‰¹ç‚¹ã€‚ å…³é”®è¯ï¼šâ€œæ¯”â€å—æ¯”è¾ƒå¥ï¼›â€œæœ‰â€å—æ¯”è¾ƒå¥ï¼›ç›´æŽ¥æ•™å¦æ³• Abstract: Comparative sentence is one of the sentences that is often used in daily life. In Mandarin, the comparative sentence that is often used is the comparative sentence â€œBiâ€ and the comparative sentence â€œYouâ€. Moreover, in the teaching of Mandarin, comparative sentence is also an important point, because for students whose native language is non-Mandarin, they are learning comparative sentence under the influence of their mother tongue, that in the usage of the comparative sentence errors will occur more or less.The author uses the direct teaching method to teach comparative sentence â€œBiâ€ and the comparative sentence â€œYouâ€ to the TanjungpuraÂ University students majoring Mandarin class A in batchÂ 2013, as well as using research test method to determine differences in students before and after the study. In this study, the authors know how to teach comparative sentence â€œBiâ€ and comparative sentence â€œYouâ€ well, and also know that the use of direct teaching method to teach comparative sentence â€œbiâ€ and comparative sentenceÂ â€œyouâ€ to the students has great results. Keywords: Comparative sentence â€œBiâ€; Comparative sentence â€œYouâ€; Direct teaching method